2017
DOI: 10.1017/jog.2016.139
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distributed runoff at the grounding line of a large Greenlandic tidewater glacier inferred from plume modelling

Abstract: ABSTRACT. Understanding the drivers of recent change at Greenlandic tidewater glaciers is of great importance if we are to predict how these glaciers will respond to climatic warming. A poorly constrained component of tidewater glacier processes is the near-terminus subglacial hydrology. Here we present a novel method for constraining near-terminus subglacial hydrology with application to marine-terminating Kangiata Nunata Sermia in South-west Greenland. By simulating proglacial plume dynamics using buoyant pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 83 publications
(184 reference statements)
2
77
0
Order By: Relevance
“…The high computational expense of the plume model used here means that it is not yet feasible to run the model on the timescales necessary to understand this variability, nor to run sufficient representative profiles to provide a useful understanding of the response. Previous work has suggested that intra-annual changes in the ambient stratification are small enough that plumes are relatively insensitive to these changes (Slater et al, 2017b) and that plume models forced with variations in runoff and a constant ambient stratification can qualitatively reproduce observations (Stevens et al, 2016). For these reasons, we highlight this as a limitation of the current implementation and suggest that this should be addressed in future investigations of plume behaviour.…”
Section: Plume Model and Undercuttingmentioning
confidence: 94%
See 1 more Smart Citation
“…The high computational expense of the plume model used here means that it is not yet feasible to run the model on the timescales necessary to understand this variability, nor to run sufficient representative profiles to provide a useful understanding of the response. Previous work has suggested that intra-annual changes in the ambient stratification are small enough that plumes are relatively insensitive to these changes (Slater et al, 2017b) and that plume models forced with variations in runoff and a constant ambient stratification can qualitatively reproduce observations (Stevens et al, 2016). For these reasons, we highlight this as a limitation of the current implementation and suggest that this should be addressed in future investigations of plume behaviour.…”
Section: Plume Model and Undercuttingmentioning
confidence: 94%
“…The model is based upon the fluid dynamics code Fluidity (Piggott et al, 2008), which solves the Navier-Stokes equations on a fully unstructured three-dimensional finite element mesh. The model formulation builds upon the work of Kimura et al (2013), with the addition of a large eddy simulation (LES) turbulence model (Smagorinsky, 1963) and the use of the synthetic eddy method (SEM) at the inlet (Jarrin et al, 2006). The geometry of the model is adapted to Kronebreen by setting the water depth to 100 m and initialising the model with ambient temperature and salinity profiles collected from ringed seals instrumented with GPS-equipped conductivity, temperature and depth satellite relay data loggers (GPS-CTD-SRDLs) (Boehme et al, 2009;Everett et al, 2017).…”
Section: Plume Model and Submarine Melt Ratesmentioning
confidence: 99%
“…This is likely a significant consideration with respect to the effect of melt-undercutting on calving: small melt rates distributed across the full terminus width may have a different impact on terminus stability than one or a few zones of focused melting (see below). The subglacial hydrology of tidewater glaciers remains poorly understood, but terminus morphology [38,44,45] and plume properties [53][54][55] indicate that it may lie typically between the channelized and distributed end members, with a substantial proportion of meltwater input from several broad (> 100-m diameter) subglacial channels.…”
Section: Processes Of Frontal Ablationmentioning
confidence: 99%
“…To date, models of frontal ablation have focused on one aspect of the system, either using plume models to simulate changes in ice-front geometry (e.g. [50,54]) or using specified undercut geometries to explore the impact on calving (e.g. [5,6]).…”
Section: Conclusion and Priorities For Future Researchmentioning
confidence: 99%
“…At present we have limited hydrographic observations within plumes fed by subglacial discharge [Bendtsen et al, 2015;Mankoff, 2016], resulting in most studies of coupled plumeoutlet glacier dynamics relying on time series of plumes reaching the fjord surface from time-lapse cameras [Fried et al, 2015;Schild et al, 2016;Slater et al, 2017a]. Relying on plume surface expression as a measure of subglacial discharge is inadequate for some tidewater glaciers, as plumes do not always reach the surface of a stratified fjord [Stevens et al, 2016b].…”
Section: Future Directions Towards Synthesismentioning
confidence: 99%